Brexit: What's at Stake for the Financial Sector? - Jakob Miethe; David Pothier (DIW Economic Bulletin, 2016)
The United Kingdom's exit from the European Union will have far- reaching implications for the British financial sector. London is currently the financial capital of Europe, and the UK's financial institutions benefit from passport rights that allow them to provide their services throughout the Single Market. The UK plays two key roles in the European financial system: the first as a major hub for wholesale banking activities conducted by large European banks, and the second as a major entry point for non- European capital entering the Single Market. If the UK were to lose its financial passport rights, both of these roles would be significantly diminished. This article analyzes some of the potential consequences of the UK losing its financial passport. One possibility is that the UK will push for greater integration with offshore financial centers in its Crown dependencies and overseas territories in order to compensate for the costs of Brexit. Such a move would run counter to the EU's objectives to prevent "aggressive tax planning," and may further complicate negotiations between the EU and the UK.
Keywords: F21; F32; F36; 330; Brexit; European Union; Financial Sector